2011
DOI: 10.3856/vol39-issue2-fulltext-16
|View full text |Cite
|
Sign up to set email alerts
|

Solapamiento trofico entre el lobo marino de un pelo Otaria flavescens y la pesqueria de arrastre demersal del golfo San Matias, Patagonia, Argentina

Abstract: RESUMEN.A nivel internacional, paralelo a la declinación y al colapso de pesquerías de gran escala, surgió un interés creciente por el estudio de las interacciones entre mamíferos marinos y pesquerías. El golfo San Matías (Patagonia, Argentina) es considerado un ecosistema pesquero independiente de las aguas de la Plataforma Continental Argentina, con condiciones oceanográficas y biológicas particulares. La condición de sistema semi-cerrado podría generar escenarios particulares para la interacción entre la fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
4
27
0
1
Order By: Relevance
“…2). This is in line with previous dietary studies that also reported fish to be the dominant prey items consumed by this otariid (Thompson et al 1998, Koen Alonso et al 2000, Suárez et al 2005, Romero et al 2011, Bustos et al 2012.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…2). This is in line with previous dietary studies that also reported fish to be the dominant prey items consumed by this otariid (Thompson et al 1998, Koen Alonso et al 2000, Suárez et al 2005, Romero et al 2011, Bustos et al 2012.…”
Section: Discussionsupporting
confidence: 91%
“…2). This is in line with previous dietary studies that also reported fish to be the dominant prey items consumed by this otariid (Thompson et al 1998, Koen Alonso et al 2000, Suárez et al 2005, Romero et al 2011, Bustos et al 2012.In the present study, Raneya brasiliensis was clearly the dominant prey species throughout the sampling period, since it was the most frequent and abundant fish item and contributed 75% to the IRI (Table 1) On the other hand, some authors have suggested that hake Merluccius hubbsi make an important contribution to the diet of the South American sea lions from Patagonia, after analysis of the stomach contents of individuals found dead on the beach or recovered from incidental catches (Koen Alonso et al , Romero et al 2011). However, in other studies based on scat analysis, including the present one, hake was shown to be absent or poorly represented in the diet of Otaria flavescens (Table 2) (Suárez et al 2005, Bustos et al 2012).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…seRgeant, 1973) and has also been suggested specifically for O. flavescens (Ximénez, 1976;geoRge-nascimento et al, 1985). To date dietary studies of O. flavescens populations distributed along the Argentine coast are scarce and most of them have reported preliminary conclusions (Koen alonso et al, 2000;suáRez et al, 2005;DRago et al, 2010;RomeRo et al, 2011). Thus, this is the first detailed study that reports the winter and spring diet of O. flavescens on the Patagonian coast.…”
mentioning
confidence: 99%